1992
DOI: 10.1111/j.0022-3646.1992.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF VARIATION IN TEMPERATURE. I. ON THE BIOCHEMICAL COMPOSITION OF EIGHT SPECIES OF MARINE PHYTOPLANKTON1

Abstract: The influence of temperature on the biochemical composition of eight species of marine phytoplankton was investigated. Thalassiosira pseudonana Hasle and Heim‐dal, Phaeodactylum tricornutum Bohlin and, Pavlova lutheri Droop (three of eight species studied) had minimum values of carbon and nitrogen quotas at intermediate temperatures resulting in a broad U‐shaped response in quotas over the temperature range of 10 to 25°C. Protein per cell also had minimum values at intermediate temperatures for six species. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
150
5
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(178 citation statements)
references
References 32 publications
19
150
5
4
Order By: Relevance
“…Furthermore, maximum growth rates were comparable to previously reported values for this strain; ∼0.9 d −1 at 18 • C and 80 µmol photons m −2 sec −1 (Li and Campbell, 2013). In contrast to other studies, we found that the thermal optimum range (17.0 and 20.1 • C, centered on 18.6 • C) was slightly colder than previously reported values (Thompson et al, 1992;Boyd et al, 2015) and may be due to the lower growth irradiance used in our study (Sandnes et al, 2005). In terms of morphological traits, absolute cell volumes were within range of previously reported values (Li and Campbell, 2013) and consistent with Thompson et al (1992), with cells becoming larger with increasing temperature (Figure 3A).…”
Section: Temperature Driven Changes In Fitness and Other Functional Tsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, maximum growth rates were comparable to previously reported values for this strain; ∼0.9 d −1 at 18 • C and 80 µmol photons m −2 sec −1 (Li and Campbell, 2013). In contrast to other studies, we found that the thermal optimum range (17.0 and 20.1 • C, centered on 18.6 • C) was slightly colder than previously reported values (Thompson et al, 1992;Boyd et al, 2015) and may be due to the lower growth irradiance used in our study (Sandnes et al, 2005). In terms of morphological traits, absolute cell volumes were within range of previously reported values (Li and Campbell, 2013) and consistent with Thompson et al (1992), with cells becoming larger with increasing temperature (Figure 3A).…”
Section: Temperature Driven Changes In Fitness and Other Functional Tsupporting
confidence: 85%
“…In contrast to other studies, we found that the thermal optimum range (17.0 and 20.1 • C, centered on 18.6 • C) was slightly colder than previously reported values (Thompson et al, 1992;Boyd et al, 2015) and may be due to the lower growth irradiance used in our study (Sandnes et al, 2005). In terms of morphological traits, absolute cell volumes were within range of previously reported values (Li and Campbell, 2013) and consistent with Thompson et al (1992), with cells becoming larger with increasing temperature (Figure 3A). These changes in cell volume, although small (i.e., ∼10%), may have significant implications for vertical export of carbon, as has been demonstrated in other small, spherical phytoplankton taxa (coccolithophores; Pantorno et al, 2013).…”
Section: Temperature Driven Changes In Fitness and Other Functional Tcontrasting
confidence: 56%
“…For example, the U-shaped pattern of cellular carbon and nitrogen, the linear pattern of increasing C : N, and the general trend of Chl a to increase and C : Chl a to decrease with increasing temperature were observed by Thompson et al (1992). The reduction in nitrogen and Chl a quotas accompanied by an increase in C : N and C : Chl a ratios for T. pseudonana grown either under N limitation or saturating light is also well documented (Eppley and Renger 1974;Berges and Harrison 1995;Reynolds et al 1997).…”
Section: Discussionmentioning
confidence: 73%
“…The observed patterns in a and a result primarily from * Chl the acclimative strategies of T. pseudonana where there is an increase in Chl a content in response to light limitation and a decrease in Chl a in response to temperature and nitrogen limitation (Sakshaug et al 1987;Thompson et al 1992;Reynolds et al 1997). Changes in the absorption cross-section of cells can be explained in terms of variations in cell size and the imaginary part of the refractive index, nЈ.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors such as temperature, light, pH, and nutrients not only affect photosynthesis and growth rate of the algae, but also influence the activity of cellular metabolism and composition. These effects have been identified individually by researchers [25][26][27][28][29][30][31], however, no consolidated review on the effect of these factors on algae is available. Most of the recent reviews have focused on production and processing techniques [11,16,32] with few data on the impacts of environmental and nutritional factors on algal growth rates.…”
Section: Introductionmentioning
confidence: 99%